African-American and Latina Women Seeking Public Health Services: Cultural Beliefs regarding Pregnancy, including Medication-taking Behavior - Luz Dalia Sanchez; Joie Rowles; David Dube (University of Minnesota Libraries Publishing, 2011)
Objective: to describe cultural beliefs and medication-taking-behavior about pregnancy in African-American and Latina women. Design: qualitative study using phenomenological methodology; face-to-face, semi structured interviews and focus group. Thematic analysis was done to obtain themes consistent with the research objective. Setting: Maricopa County, Arizona, Department of Public-health Programs, November 2008 through April 2009. Participants: women seeking public-health services in the greater Phoenix, Arizona. Results: fifteen adult women representing two ethnic groups (seven African-Americans and eight Latinas) participated. Themes derived from the interview data included: "The Dilemma: To Become or Not to Become Pregnant;" "The Ideal Stress-free World: Support System;" "Changing Worlds: Wanting Dependency;" and "The Health care System: Disconnection from Pregnancy to Postpartum." Conclusions: based on the cultural themes: 1. pregnancies were not planned; 2. healthy life-style changes were not likely to occur during pregnancy; 3. basic facts about the biology of sexual intercourse and pregnancy were not understood, and there was no usage of any preconceptional or prenatal medications; and 4. professional health care was not desired or considered necessary (except during delivery). These cultural beliefs can contribute to negative birth outcomes, and need to be considered by pharmacists and other health-care providers. The information gained from this study can guide the implementation of educational programs developed by pharmacists that are more sensitive to the cultural beliefs and points of view of these particular women. Such programs would thus be more likely to be favorably received and utilized. Type: Original Research